Phylogenomics studies and molecular markers reliably demarcate genus Pseudomonas sensu stricto and twelve other Pseudomonadaceae species clades representing novel and emended genera - Rudra, Bashudev; Gupta, Radhey S. (Frontiers in Microbiology, 2024)
Genus Pseudomonas is a large assemblage of diverse microorganisms, not sharing a common evolutionary history. To clarify their evolutionary relationships and classification, we have conducted comprehensive phylogenomic and comparative analyses on 388 Pseudomonadaceae genomes. In phylogenomic trees, Pseudomonas species formed 12 main clusters, apart from the “Aeruginosa clade” containing its type species, P. aeruginosa. In parallel, our detailed analyses on protein sequences from Pseudomonadaceae genomes have identified 98 novel conserved signature indels (CSIs), which are uniquely shared by the species from different observed clades/groups. Six CSIs, which are exclusively shared by species from the “Aeruginosa clade,” provide reliable demarcation of this clade corresponding to the genus Pseudomonas sensu stricto in molecular terms. The remaining 92 identified CSIs are specific for nine other Pseudomonas species clades and the genera Azomonas and Azotobacter which branch in between them. The identified CSIs provide strong independent evidence of the genetic cohesiveness of these species clades and offer reliable means for their demarcation/circumscription. Based on the robust phylogenetic and molecular evidence presented here supporting the distinctness of the observed Pseudomonas species clades, we are proposing the transfer of species from the following clades into the indicated novel genera: Alcaligenes clade – Aquipseudomonas gen. nov.; Fluvialis clade – Caenipseudomonas gen. nov.; Linyingensis clade – Geopseudomonas gen. nov.; Oleovorans clade – Ectopseudomonas gen. nov.; Resinovorans clade – Metapseudomonas gen. nov.; Straminea clade – Phytopseudomonas gen. nov.; and Thermotolerans clade – Zestomonas gen. nov. In addition, descriptions of the genera Azomonas, Azotobacter, Chryseomonas, Serpens, and Stutzerimonas are emended to include information for the CSIs specific for them. The results presented here should aid in the development of a more reliable classification scheme for Pseudomonas species.